Decoding the selective chemical modulation of CYP3A4 - Wang, Jingheng; Nithianantham, Stanley; Chai, Sergio C.; Jung, Young-Hwan; Yang, Lei; Ong, Han Wee; Li, Yong; Zhang, Yifan; Miller, Darcie J.; Chen, Taosheng (Nature communications, 2025)
Drug-drug interactions associate with concurrent uses of multiple medications. Cytochrome P450 (CYP) 3A4 metabolizes a large portion of marketed drugs. To maintain the efficacy of drugs metabolized by CYP3A4, pan-CYP3A inhibitors such as ritonavir are often co-administered. Although selective CYP3A4 inhibitors have greater therapeutic benefits as they avoid inhibiting unintended CYPs and undesirable clinical consequences, the high homology between CYP3A4 and CYP3A5 has hampered the development of such selective inhibitors. Here, we report a series of selective CYP3A4 inhibitors with scaffolds identified by high-throughput screening. Structural, functional, and computational analyses reveal that the differential C-terminal loop conformations and two distinct ligand binding surfaces disfavor the binding of selective CYP3A4 inhibitors to CYP3A5. Structure-guided design of compounds validates the model and yields analogs that are selective for CYP3A4 versus other major CYPs. These findings demonstrate the feasibility to selectively inhibit CYP3A4 and provide guidance for designing better CYP3A4 selective inhibitors. To maintain the efficacy of drugs metabolized by CYP3A4, pan-CYP3A inhibitor is often co-administered, but the high homology between CYP3A4 and CYP3A5 has hampered the development of selective CYP3A4 inhibitors. Here, the authors report a series of selective CYP3A4 inhibitors and show that differential C-terminal loop conformations and two distinct ligand binding surfaces disfavour the binding of selective CYP3A4 inhibitors to CYP3A5.